Implementation and Operational Research: Uptake of Services and Behaviors in the Prevention of Mother-to-Child HIV Transmission Cascade in Zimbabwe. (1st June 2015) - McCoy, Sandra I.; Buzdugan, Raluca; Padian, Nancy S.; Musarandega, Reuben; Engelsmann, Barbara; Martz, Tyler E.; Mushavi, Angela; Mahomva, Agnes; Cowan, Frances M.
Abstract : Objective: To examine the uptake of services and behaviors in the prevention of mother-to-child HIV transmission (PMTCT) cascade in Zimbabwe and to determine factors associated with MTCT and maternal antiretroviral therapy (ART) or antiretroviral (ARV) prophylaxis. Design: Analysis of cross-sectional data from mother–infant pairs. Methods: We analyzed baseline data collected in 2012 as part of the impact evaluation of Zimbabwe's Accelerated National PMTCT Program. Using multistage cluster sampling, eligible mother–infant pairs were randomly sampled from the catchment areas of 157 facilities in 5 provinces, tested for HIV infection, and interviewed about PMTCT service utilization. Results: Of 8800 women, 94% attended ≥1 antenatal care visit, 92% knew their HIV serostatus during pregnancy, 77% delivered in a health facility, and 92% attended the 6–8 week postnatal visit. Among 1075 (12%) HIV-infected women, 59% reported ART/ARV prophylaxis and 63% of their HIV-exposed infants received ARV prophylaxis. Among HIV-exposed infants, maternal receipt of ART/ARV prophylaxis was protective against MTCT [adjusted prevalence ratio (PRa ): 0.41, 95% confidence interval (CI): 0.23 to 0.74]. Factors associated with receipt of maternal ART/ARV prophylaxis included ≥4 antenatal care visits (PRa : 1.18, 95% CI: 1.01 to 1.38), institutional delivery (PRa : 1.31, 95% CI: 1.13 to 1.52), and disclosure of serostatus (PRa : 1.30, 95% CI: 1.12 to 1.49). Conclusions: These data from women in the community indicate gaps in the PMTCT cascade before the accelerated program, which may have been missed by examination of health facility data alone. These gaps were especially noteworthy for services targeted specifically to HIV-infected women and their infants, such as maternal and infant ART/ARV prophylaxis.